Comparison of external load during differing microcycle structures across two competitive seasons in elite female Portuguese soccer players - Oliveira, Rafael; Brito, João Paulo; Fernandes, Renato; Espada, Mário C.; Santos, Fernando J.; Nalha, Matilde; Zmijewski, Piotr; Morgans, Ryland (Frontiers in Sports and Active Living, 2025)
This study aimed to: (i) compare the accumulated load between three and four training sessions per week plus a match across two consecutive seasons in elite female soccer players, and (ii) compare the training/match ratio (TMr) of external load. Data from 10 players in each season were analysed during the study period. The microcycle structure of the first season included three training sessions (3dW) and a match per week, while the second season included four training sessions (4dW) plus a match per week. The following measures were used for analysis: duration, total distance, high-speed running distance (HSR, > 15 km/h), number of accelerations (ACC, > 1–2 m.s−2 [ACC1]; > 2–3 m.s−2 [ACC2]; > 3–4 m.s−2 [ACC3]; > 4 m.s−2 [ACC4]) and decelerations (DEC, < 1–2 m.s−2 [DEC1]; < 2–3 m.s−2 [DEC2];< 3–4 m.s−2 [DEC3];< 4 m.s−2 [DEC4]). The accumulated load was calculated by summing key metrics for all training sessions and matches, while TMr was calculated by dividing the accumulated load by match data. The main results showed that all variables showed meaningful differences (p < 0.05) except for ACC4 and DEC4. Specifically, total distance was higher in 3dW than 4dW (p = 0.007), while the remaining variables were higher during 4dW. Moreover, all TMr were higher in 4dW than 3dW (p < 0.001 for all variables except for ACC4 and DEC4). As expected, this study showed that adding one training session per week increased accumulated load and TMr for several key variables.